Recent Developments in Cancer Systems Biology - Sinha, Raghu; Arga, Kazim Yalcin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This ebook includes original research articles and reviews to update readers on the state of the art systems approach to not only discover novel diagnostic and prognostic biomarkers for several cancer types, but also evaluate methodologies to map out important genomic signatures. In addition, therapeutic targets and drug repurposing have been emphasized for a variety of cancer types. In particular, new and established researchers who desire to learn about cancer systems biology and why it is possibly the leading front to a personalized medicine approach will enjoy reading this book.